New strain of sweetpotato whitefly invades California vegetables - Thomas Perring; Arthur Cooper; Dave J. Kazmer; Clyde Shields; Jon Shields (California Agriculture, 1991)
In 1990, a new strain of sweetpotato whitefly invaded Southern California agricultural regions, inflicting heavy damage on cruciferous crops, Problems related to this new strain have impacted vegetable growers throughout California and other growing regions. In the Imperial Valley, 95% of the 1991 fall melons were disced and total losses to summer and fall crops have been estimated at over $120 million.